2009
DOI: 10.1039/b918750b
|View full text |Cite
|
Sign up to set email alerts
|

Emission quench of water-soluble ZnS–AgInS2 solid solution nanocrystals and its application to chemosensors

Abstract: Redox-dependent emission quenching of low toxic ZnS-AgInS(2) semiconductor nanocrystals was studied and the obtained behavior was found to be applicable to fabrication of fluorescent biosensors in combination with redox enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…76c demonstrates PL recovery behavior when glucose of different concentrations, ranging from 5 to 20 lM, was added to the solution. The emission intensity increases with glucose concentration, indicating that this system enables quantitative detection of glucose [452].…”
Section: Biosensorsmentioning
confidence: 93%
See 1 more Smart Citation
“…76c demonstrates PL recovery behavior when glucose of different concentrations, ranging from 5 to 20 lM, was added to the solution. The emission intensity increases with glucose concentration, indicating that this system enables quantitative detection of glucose [452].…”
Section: Biosensorsmentioning
confidence: 93%
“…which are normally used in the conventional methods. By controlling the PL quenching behaviors, Uematsu and co-workers developed a highly photoluminescent ZnS-AgInS 2 solid solution (ZAIS) NCs for sensing glucose [452]. They fabricated a glucose-sensing system by combining the redox-dependent quenching of MPA-ZAIS with a redox enzyme, as illustrated in Fig.…”
Section: Biosensorsmentioning
confidence: 99%
“…The magnitudes of quenching evaluated as I 0 /I ¹ 1 were 90 times different between its redox states, where I 0 and I are PL intensity in the absence and presence of quenchers, respectively. Another candidate is monovalent MP + used in our previous investigation on glucose sensing, 14 because MP + also loses the quenching ability by the reduction to neutral MPH. Figure 3(a) shows the time course PL intensity variation of MPA-ZAIS NPs solution (1 µM in terms of particle) in the presence of TMPDA (30 µM) when the potential of a Pt mesh electrode illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 On the other hand, PL quenching by a photoinduced electron transfer to redox species is known as another mechanism that has higher sensitivity as to detect the adsorption of a single molecule on one NP. [12][13][14][15][16][17] The rate of electron transfer is very amenable to the changes in distance around 1 nm that is shorter than the distance needed for the FRET. We demonstrated that the polarity of both NPs and quenchers in aqueous solution profoundly affects the efficiency of the electron transfer by virtue of variations in the electrostatic force between the two species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation